Premature menopause and severity of coronary artery disease - Nasri, Hamidreza (Medknow Publications Pvt Ltd, 2011)
BACKGROUND: Relationship between premature menopause and presence, severity and life-threatening events of coronary artery disease (CAD) has been suggested in recent observations. The present study tried to assess relationship between age of menopause and severity of CAD in a sample of women with suspected CAD. METHODS: In a cross-sectional study, we included 189 consecutive women with suspected CAD that were candidate for coronary angiography and admitted to the Shafa hospital in Kerman city. Our final population for analysis included women who underwent natural menopause (n = 148) or premature menopause (n = 41). CAD severity was classified according to the number of coronary artery stenosis ≥ 50% in coronary angiography. RESULTS: Among 189 study patients with suspected CAD, 22.0% of those with early menopause and 23.6% of those with normal menopause suffered three coronary vessels involvement, while normal angiography features was shown in 39.0%o and 40.5%>, respectively. Regarding severity of CAD and left main lesions, no significant differences were found between the patients with and without premature menopause. According to the multivariable logistic regression model and with the presence of other patients’ variables as cofounders, age of menopause could not predict the presence and severity of CAD in patients with suspected CAD. However, patients’ age (OR: 1.11, p < 0.001) and family history of CAD (OR: 2.05, p = 0.04) were main predictors of the severity of CAD in these patients. CONCLUSIONS: Premature menopause does not predict occurrence or severity of CAD in women with suspected CAD, but women age and their family history of CAD are main predictors of the severity of CAD.